2015
DOI: 10.1016/j.ajpath.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotective Effects of IL-33/ST2 Link to Osteoclast Apoptosis

Abstract: The relevance of IL-33 and its receptor ST2 for bone remodeling is not well-defined. Our aim was to assess the role and underlying mechanisms of IL-33/ST2 in mechanically induced bone remodeling. BALB/c (wild type) and ST2 deficient (St2(-/-)) mice were subjected to mechanical loading in alveolar bone. Microtomography, histology, and real-time quantitative PCR were performed to analyze bone parameters, apoptosis and bone cell counts, and expression of bone remodeling markers, respectively. MC3T3-E1 osteoblasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
6
33
0
Order By: Relevance
“…Moreover, there are multiple mechanisms for estrogen effects on bone cells, such as a blockade of osteoclast differentiation and activation, and an increase in the rate of apoptosis . We observed that the OTM and osteoclast numbers were increased in both ST2 −/− and OVX WT mice, confirming the osteoprotective effects of IL‐33 and estrogen on alveolar bone remodeling . However, our findings showed that under the condition of estrogen deficiency, a similar amount of tooth movement was observed in ST2 −/− OVX mice compared with that in WT OVX and ST2 −/− ‐intact mice.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Moreover, there are multiple mechanisms for estrogen effects on bone cells, such as a blockade of osteoclast differentiation and activation, and an increase in the rate of apoptosis . We observed that the OTM and osteoclast numbers were increased in both ST2 −/− and OVX WT mice, confirming the osteoprotective effects of IL‐33 and estrogen on alveolar bone remodeling . However, our findings showed that under the condition of estrogen deficiency, a similar amount of tooth movement was observed in ST2 −/− OVX mice compared with that in WT OVX and ST2 −/− ‐intact mice.…”
Section: Discussionsupporting
confidence: 58%
“…2 In our study, ovariectomy and the lack of ST2 decreased the osteoblast number at the distal side of the OTM, which is in agreement with the literature. 15 However, in the presence of both estrogen and ST2 (WT-intact mice) or in their complete absence (ST2 −/− OVX mice), the osteoblast count recovered in the maxillary bone. These results suggest that there is an unclear underlying mechanism through which IL-33 plays a role in osteoblast downregulation in the alveolar bone due to a lack of estrogen.…”
Section: St2 −/− Ovx Mice Have Increased Levels Of Il-10 and Sema3amentioning
confidence: 99%
See 2 more Smart Citations
“…[62] Similarly, under OTM, ERαKO mice show an increase in the RANKL/OPG ratio, RANK, IL-6, and ST2, as well as decreased expression of dentin matrix acidic phosphoprotein and alkaline phosphatase in periodontal tissue. [63] Estrogen deficiency affects the rate of alveolar bone remodeling overall and secondarily the rate of experimental tooth movement, as shown in ovariectomized (OVX) rats undergoing lateral orthodontic tooth movement, where OVX specimens showed significantly (p<.001) increased rates of experimental tooth movement. [64, 56]…”
Section: Osteoporosis Tooth Movement and Earr In Orthodonticsmentioning
confidence: 99%